The Friction Angle of the Leiyang Marble Surface after Exposure to High Temperature - Meng Hong Peng; Man Huang (Advances in Civil Engineering)
There is a lack of information about the temperature-dependent nature of the rock surface, which is one of the essential parameters to predict the surface friction. In the present study, we experimentally study the effect of temperature on the basic friction angle of the marble surface through the direct shear test under the low normal loading condition and tilting test (Stimpson/disk tilt test). The basic friction angle gradually decreases with the increase in temperature from 20°C to 600°C for the two kinds of the tilting test. The results indicate that the Stimpson test on samples with the length-to-diameter ratio of 2 can be more reliable to estimate the basic friction angle of the rock surface after exposure to high temperatures. The results illustrate that the sliding angle depends on the surface condition. With the increase in the repetitive measurements, the sliding angle decreases as the marble surface is cleaned, and the parameter increases as the marble surface is not cleaned.